High School Students’ Mental Models on Chemical Equilibrium - Hilya Ulinnaja; Subandi Subandi; Muntholib Muntholib (Pascasarjana Universitas Negeri Malang (UM), 2019)
Abstract: Chemical equilibrium knowledge has many abstract concepts that often lead to alternative conceptions and misconceptions. One way that can be used to find out students’ conceptions is to identify their mental models.The purpose of this study was to investigate students’ mental models in understanding knowledge of chemical equilibrium. This study applied a survey research design. The subjects were 12thgrade high school students consisting of 181 students distributed into 5 classes. Da-ta was collected through a written test using the Mental Models Test on Chemical Equilibrium (M2T-CE) consisting of 18 two-tier multiple choice items. Data analysis was performed by categorizing stu-dent’ mental models into initial, synthetic and scientific mental models. The results showed that 51.60% of respondents had a scientific mental model, 23.52% of them had a synthetic mental model, and 24.88% of others had an initial mental model. Whereas the respondents’ average score of chemical equilibrium mental models was 63.36 from a maximum score of 100. This score belongs to the good category.Key Words: initial mental models, synthetic mental models, scientific mental models, chemical equilibriumAbstrak: Pengetahuan kesetimbangan kimia memiliki banyak konsep abstrak yang sering mengarah pada konsepsi alternative dan kesalahpahaman. Salah satu cara yang dapat digunakan untuk mengetahui konsepsi siswa adalah untuk mengidentifikasi model mental mereka. Tujuan penelitian ini adalah untuk menyelidiki model mental siswa dalam memahami pengetahuan tentang kesetimbangan kimia. Penelitian menggunakan desain penelitian survei. Subjek penelitian adalah siswa SMA kelas 12 yang terdiri dari 181 siswa yang didistribusikan ke dalam 5 kelas. Data dikumpulkan melalui tes tertulis menggunakan Tes Model Mental pada Kesetimbangan Kimia (M2T-CE) yang terdiri dari 18 item pilihan ganda dua tingkat. Analisis data dilakukan dengan mengelompokkan model mental siswa ke dalam model mental awal, sintetis dan ilmiah. Hasil penelitian menunjukkan bahwa 51,60% responden memiliki model mental ilmiah, 23,52% dari mereka memiliki model mental sintetik, dan 24,88% lainnya memiliki model mental awal. Sedangkan skor rata-rata responden dari model mental kesetimbangan kimia adalah 63,36 dari skor maksimum 100. Skor ini termasuk dalam kategori baik.Kata kunci: model mental awal, model mental sintetik, model mental ilmiah, kesetimbangan kimia